Revised kuppuswamy scale for 2021 based on new consumer price index and use of conversion factors - Syed Najmul Ain; Zahid Ali Khan; Mohamad Azhar Gilani (Wolters Kluwer Medknow Publications, 2021)
One of the factors that affect the health of the people is the socioeconomic class. One of the widely used scales for measuring socioeconomic status is the Kuppuswamy scale originally developed in 1976. It must be updated with time as it takes family income into account. The revision of income can be done by using Consumer price index for industrial workers. Conversion factors were given by earlier researchers whenever the base year changed to update the scale. Since the base year has now been changed to 2016, we are giving conversion factor to be multiplied with income categories of 2001 to get the updated scale. We have shown how to calculate the conversion factors and when they are required. We have deducted a conversion factor of 3.26 which is to be multiplied with income categories of 2001 to get the updated scale for February 2021.